PERAN AKTOR DALAM PERCEPATAN PROGRAM PEREMAJAAN SAWIT RAKYAT DI KABUPATEN INDRAGIRI HILIR - Minda Putri Carolina; Mayarni Mayarni (ADMIN: Jurnal Administrasi Negara, 2024)
The People's Palm Oil Replanting Program (PSR) is an initiative to promote the development of community plantations, including government support in the form of investment credit and interest subsidies. This research focuses on the actors' roles in accelerating the implementation of the People's Palm Oil Replanting Program in the Indragiri Hilir Regency. This study aims to understand the functions of each party involved and the inhibiting factors in accelerating the People's Palm Oil Replanting Program in the Indragiri Hilir Regency. The research method used is qualitative, descriptive research employing Blackman's theory (2003),which consists of four variables: Informants, Consultants, Cooperation, and Control. The findings reveal that the roles of the actors are not yet optimal, there is a lack of found partners to assist farmer groups, and limitations in knowledge, funding, and inadequate infrastructure are inhibiting factors in accelerating the People's Palm Oil Replanting Program in the Indragiri Hilir Regency. This research suggests that the involved actors are expected to be more optimal in their respective roles